Headspace solid-phase microextraction-gas chromatography–mass spectrometry for the determination of volatile and semi-volatile substances in sebum as biomarkers for Parkinson's disease - Zschiesche, Annette; Hummel, Thomas; Power-Guerra, Nicole; Haehner, Antje; Falkenburger, Björn; Koch, Susanne; Broesamle, Jakob; Schulz, Katja (Microchemical journal, 2025)
This study analyzed the chemical components of sebum from Parkinson's disease patients and a healthy control group using headspace solid-phase microextraction-gas chromatography–mass spectrometry (HS-SPME-GC–MS). This method requires minimal sample amount, minimal sample preparation and no extensive equipment. The extraction efficiency of six commercially available fibers was thoroughly evaluated. Among these, a 65 μm polydimethylsiloxane/divinylbenzene coating emerged as the most effective for extracting key biomarkers: perillic aldehyde, eicosane, and octadecanal. To maximize the efficiency of the headspace solid-phase microextraction procedure, several critical parameters were optimized. These included extraction temperature and duration, as well as desorption temperature and time. This comprehensive optimization process ensured the most suitable conditions for biomarker extraction and analysis. The investigation included 80 subjects, comprising 28 healthy control group and 52 Parkinson's disease patients. The compounds perillic aldehyde, eicosane and octadecanal, which were first detected in this context by Trivedi et al. were investigated. Notably, perillic aldehyde was identified as potential biomarker, while eicosane and octadecanal showed no significant differences between the two groups. Statistical analysis using the Wilcoxon-Mann-Whitney test confirmed significant differences for perillic aldehyde (p = 0.00154). Method validation demonstrated high precision and accuracy of measurements, with confirmed intraday and interday stability. •Perillic aldehyde was identified as potential biomarker with significant differences between the patient group and the healthy control group.•HS-SPME-GC–MS method requires minimal sample amount, minimal sample preparation and no extensive equipment.•Method provides robust validation results across multiple analytical parameters.